Soldiers and diplomacy in Burma understanding the foreign relations of the Burmese praetorian state - Egreteau, Renaud; Jagan, Larry (NUS Press in association with IRASEC, 2013)
Soldiers and Diplomacy addresses the key question of the ongoing role of the military in Burma's foreign policy. The co-authors, a political scientist and a former top Asia editor for the BBC, provide a fresh perspective on Burma's foreign and security policies, which have shifted between pro-active diplomacies of neutralism and non-alignment, and autarkical policies of isolation and xenophobic nationalism. The authors argue that key elements of continuity underlie Burma's striking postcolonial policy changes and contrasting diplomatic practices, Among the defining factors here are the formidable dominance of the Burmese armed forces over state structure, the enduring domestic political conundrum and the peculiar geography of a country located at the crossroads of India, China and Southeast Asia. The authors argue that the Burmese military still has the tools needed to retain their praetorian influence over the country's foreign policy in the post-junta context of the 2010s. For international policymakers, potential foreign investors and Burma's immediate neighbors, this will have strong implications in terms of the country's foreign policy approach.